A PROTOTYPE OF DIGITAL LIBRARY APPLICATION USING MICROFRAMEWORK FLASK - Ridha Sefina Samosir; Ester Lumba; Poltak Pancarian Situmorang (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2022)
Covid-19 encourages the use of Digital Library sources. especially for students who are completing college assignments, students who are preparing their final project, lecturer in compling teaching material, including researchers. On the other hand, technology has developed rapidly. Technological developments have changed the pattern of human life and changed the business models of various organizations in order to survive in this digital era. However, there are still many organizations have not optimized the use of technology. One example is a university that does not yet have a Digital Library. This prompted the research team to conduct research on how to build a Digital Library. This study uses the Extreme programming (XP) software development method. This study aims to design a Digital Library prototype using a Microframework Flask. This research is expected to be a reference or model in developing digital libraries.